Internal dosimetry of 99mTc-Androctonus crassicauda scorpion venom complex using MCNP simulation code and MIRD method for cancer diagnostic and therapeutic purposes: Internal dosimetry of 99mTc-Androctonus crassicauda scorpion venom - Valipour Yekany, Leila; Babapour Mofrad, Farshid; Shirmardi, Seyed Pezhman; Erfani, Mostafa; Zare Mirakabadi, Abbas (Archives of Advances in Biosciences, 2021)
Introduction: Due to the increasing progress of cancer, the view of paying attention to the rich resources in nature such as animal venom has been considered by researchers due to less side effects than existing treatments. Therefore, the tissue distribution of radionuclide-venom complex in laboratory animals and the internal dosimetry of the organs are of great importance for the clinical diagnostic and therapeutic purposes of cancer. Methods: In this study, after biological distribution of 99mTc-venom complex and calculation of %ID/g, accumulation activity, dosimetry estimation steps were obtained and human data were extracted from the Sparks-Idogan formula. Then effective dose calculation was performed using MIRD analysis method and MCNP simulation code. Result: The dose of 99mTc-venom in different organs of the human body was calculated based on the distribution of information in the rat body using the MIRD analysis method and the MCNP simulation code. The highest and the lowest effective dose respectively delivered to the heart wall (with 3.47E-05 and 4.05E-05 mSv/MBq) and the testic(0.05E-06 and 0.08E-06 mSv/MBq). Conclusion: Considering the antitumor effect of Andro ctonus crassicauda scorpion venom according to recent research, we hope that the results of biological distribution and internal dosimetry 99mTc-venom in this research will be a step the clinical diagnostic and therapeutic purposes of cancer using natural products in the future .